Mammon and God: Mapping Flannery O’Connor’s Atlanta - Luttrull, Daniel (Christianity & literature, 2017)
In “The Artificial Nigger,” Flannery O’Connor provides directions for the reader to precisely follow her characters’ circuitous route from the city center to the suburban train station where they end their journey. While the Heads find themselves in three of the city’s shopping centers, O’Connor is careful to keep them from coming within sight of any of the city’s churches. O’Connor uses this commercialized Atlanta to examines the claim that commerce can make people “too busy to hate.” She then moves into an allegorical register in which the market represents judgement and the Heads experience grace only after leaving it.